Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fnut.2022.956310
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, correlates, and gender disparities related to eating disordered behaviors among health science students and healthcare practitioners in Lebanon: Findings of a national cross sectional study

Abstract: BackgroundThe raised prevalence of eating disorders (ED) amongst health science students and health professionals is of mounting concern. This study aims to determine the prevalence and correlates of eating disorders risk amongst a sample of Lebanese health science students and healthcare practitioners of both genders.MethodsThis cross-sectional study enrolled a convenient sample of 1,000 participants (mean age: 23 ± 5.4; females: 74.9%) from faculties of health sciences, clinics, pharmacies, and hospitals. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
1
0
0
Order By: Relevance
“…A study done by Lebanese health science students and healthcare practitioners showed that the prevalence of eating disorders risk was 22.5% and about 80% of female students were high risk. 22 The existing literature also supports the finding in the reported case.…”
Section: Discussionsupporting
confidence: 88%
“…A study done by Lebanese health science students and healthcare practitioners showed that the prevalence of eating disorders risk was 22.5% and about 80% of female students were high risk. 22 The existing literature also supports the finding in the reported case.…”
Section: Discussionsupporting
confidence: 88%